Story of my death - Font, Ferran; Verdaguer, Marc ca. 20. Jh; Robinson, Joe; Juncà, Enric (Second Run, 2015)
"His deliciously eccentric film "The Story of My Death" (winner of the prestigious Golden Leopard prize at the 2013 Locarno Film Festival) imagines a meeting between the ageing Casanova and Count Dracula to chart the collision between the eighteenth century of Enlightenment, rationalism and libertine sensuality and a nineteenth century founded upon Romanticism, obscurantism and violence." [amazon.co-uk]
Original: Frankreich, Spanien, Rumänien 2013
Special features: presented from a new high-definition digital transfer, approved by the director ; Cuba Libre (2013): Serra’s exquisite short film - a tribute to filmmaker Rainer Werner Fassbinder ; 16-page booklet featuring a wide-ranging conversation between Albert Serra and filmmaker Ben Rivers ; new and improved English subtitle translation ; 5.1 Dolby Digital Surround audio option
Bildformat 2.35:1 (anamorph)
Keywords: Film; DVD-Video